MECOPE: Multifocal excitation compressive-sensing photoacoustic endomicroscopy through a multimode fibre - Tianrui Zhao; Edward Zhang; Paul C. Beard; Wenfeng Xia (Photoacoustics)
Photoacoustic endoscopy has gained intensive research interest in recent years, particularly for guiding minimally invasive procedures in several clinical disciplines including oncology, cardiology and fetal medicine. Multimode fibres hold the potential to revolutionise medical endoscopy with ultrathin size and micrometre-level resolution. Compared to conventional endomicroscopes based on multi-core fibre bundles, multimode fibres-based endoscopes offer significantly higher spatial resolution, smaller diameters, and lower costs. However, current implementations of multimode fibre imaging, whether using raster-scan or speckle compressive sensing imaging, are hindered by limitations in frame rate or signal-to-noise ratio. In this work, we developed a multifocal excitation compressive-sensing photoacoustic endomicroscopy system that combines wavefront shaping-based light focusing with compressive sensing to achieve high imaging speed without compromising image quality. The method was validated through numerical simulations and experiments with carbon fibre phantoms and red blood cells ex vivo. Our results demonstrated comparable image quality to raster-scan-based imaging, while improving the frame rate by a factor of 5, reaching 11.5 frames per second. With further enhancements in focusing performance and the use of a higher repetition rate laser, this method shows promise for achieving real-time, high-resolution endomicroscopy through ultrathin probes, making it a valuable tool for guiding minimally invasive procedures.